Standardization of Dosages of Sulphuric Acid and Duration for Delinting of Cotton Hybrid DCH-32 Seeds - SHIVAYOGI Y. RYAVALAD; N.K. BIRADARPATIL; M. SHEKHARGOUDA; I.S. KATAGERI (Seed Research, 2026)
The seeds of DCH-32 hybrid cotton were subjected to delinting by using different quantity of H₂SO₄ (60, 80, 100 and 120 ml/kg of seed) with different duration (2, 4, 6, 8, 10, 12 and 14 min). The delinting of hybrid cotton seeds with the dosage of 100 ml H₂SO₄ per kg of seed treated for 10 min was better, as the fuzz removal was complete and the seeds recorded higher germination with other quality parameters.